2022
DOI: 10.1094/phyto-02-21-0069-r
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Single Core Gene, tssM, of Type VI Secretion System of Xanthomonas perforans Influences Virulence, Epiphytic Survival, and Transmission During Pathogenesis on Tomato

Abstract: Xanthomonas perforans is a seed-borne hemi-biotrophic pathogen that successfully establishes infection in the phyllosphere of tomato. While the majority of the studies investigating mechanistic basis of pathogenesis have focused on successful apoplastic growth, factors important during asymptomatic colonization in the early stages of disease development are not well understood. In this study, we show that tssM gene of the type VI secretion system cluster i3* (T6SS-i3*) plays a significant role during initial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 67 publications
4
15
0
Order By: Relevance
“…The type VI secretion system (T6SS) in plant pathogenic bacteria has antimicrobial ability; they are used to directly inject toxins into competitor bacteria cells to reduce competition for resources ( Bernal et al, 2018 ). The contribution of T6SS in plant host interactions, however, has not yet been investigated ( Liyanapathiranage et al, 2021 ). A cluster of thirteen type six secretion genes, tssA-tssM , encode the system and were formerly referred to as imp ( imp aired in nitrogen fixation) genes.…”
Section: Resultsmentioning
confidence: 99%
“…The type VI secretion system (T6SS) in plant pathogenic bacteria has antimicrobial ability; they are used to directly inject toxins into competitor bacteria cells to reduce competition for resources ( Bernal et al, 2018 ). The contribution of T6SS in plant host interactions, however, has not yet been investigated ( Liyanapathiranage et al, 2021 ). A cluster of thirteen type six secretion genes, tssA-tssM , encode the system and were formerly referred to as imp ( imp aired in nitrogen fixation) genes.…”
Section: Resultsmentioning
confidence: 99%
“…The type VI secretion system (T6SS) is defined as a cell envelope‐spanning machine that bacteria use to translocate toxic effector proteins into eukaryotic and prokaryotic cells (Costa et al, 2015 ). Recent works have demonstrated that the T6SS is involved in virulence or bacterial competition in several Xanthomonas pathogens (Choi et al, 2020 ; Liyanapathiranage et al, 2022 ; Montenegro Benavides et al, 2021 ; Zhu et al, 2020 ). Here, the transcription profile showed that the HpaP in Xoo and Xoc affects the T6SS.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary history of X. axonopodis complex has been recently well studied, where it has been proposed that the first step of generalist diversification into the X. axonopodis subgroups was followed by the second step of ecology-driven specialization that favored the emergence of novel pathovars ( Mhedbi-Hajri et al, 2013 ). Given our prior work that suggested the potential role of core gene tssM of cluster T6 i3*, in overall epiphytic fitness in X. perforans and during initial stages of disease development ( Liyanapathiranage et al, 2021 ), we hypothesized that during diversification into X. axonopodis subgroups, a combination of specific T6SS clusters in individual species provided significant advantage during the process of niche adaptation onto specific hosts. We closely examined the patterns of the evolutionary history of the i3* and i3*** T6 clusters in the X. axonopodis complex subspecies groups and the lifestyle of these pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The role of i3* has been suggested not only in competition against resident flora, more specifically, resistance to predation by the bacterivorous amoeba, Dictyostelium discoideum , but also in adaptation to the phyllosphere non-vascular environment ( Bayer-Santos et al, 2018 ; Liyanapathiranage et al, 2021 ). Loss of i3* in lineages containing X. oryzae and X. vasicola , both vascular pathogens, might be in response to the vascular lifestyle.…”
Section: Discussionmentioning
confidence: 99%